Steps to better understanding resistant behaviours in hospitalised patients with dementia. (23rd August 2019) - Cook, Rob; Lamont, Tara; Martin, Rosie
The study: Featherstone K, Northcott A, Harden J, et al. Refusal and resistance to care by people living with dementia being cared for within acute hospital wards: an ethnographic study. Health Serv Deliv Res 2019;7. This study was funded by the National Institute for Health Research Health Services and Delivery Research Programme (project number 13/10/80). To read the full NIHR Signal, go to https://discover.dc.nihr.ac.uk/content/signal-000779/understanding-dementia-care-in-hospitals